Barriers and Facilitators of Access to Psychological Services for Indigenous Populations: A Scoping Review and Thematic Analysis - Plessas, Anna; Billot, Moana W.; Tamatea, Armon; Medvedev, Oleg N.; McCormack, Jessica; Anderson, Angelika (Frontiers in Psychiatry, 2021)
Background: The extent to which behavior-analytic interventions are offered to Indigenous populations across CANZUS in accessible and culturally appropriate ways is unknown. We conducted a scoping review with a thematic analysis of the extant literature to find: (1) what are the barriers and facilitators for providing effective and equitable delivery of psychological services (with a behavioral component) to Indigenous populations; and (2) what tools and practices exist for an effective and equitable service delivery. Methods: We systematically reviewed Medline, CINAHL, PubMed, PsychInfo, Web of science, Ovid and INNZ databases between 1990 and 2020. For the scoping review, we adhered to the JBI methodological approach (2015) and the PRISMA strategy for the identification, selection, and appraisal of the reviewed articles. A total of 1265 unique articles met the criteria for the screening by title; 238 by abstract; 57 were included for full text assessment; and 37 were included in the final analysis. Results: Three themes were revealed to account for the barriers and facilitators of culturally friendly practices: 1) connecting practices are about interactions shaping the relationship between service provider and service client; 2) innovative practices test new approaches and innovations that could facilitate access to psychological services and overcome barriers, and 3) reflective practices are about critically examining the processes and actions undertaken towards effective cultural adaptation of services. Conclusions: Our analysis suggests that the level of success in bringing together services and the recipients of treatment (connection), showing flexibility and persistence in finding solutions (innovation) and examining the role of our behaviors in reaching our goals (reflection) is determined by the providers’ action in the aforementioned three dimensions of practice.